Characterization of thermo-physical and hardness properties of unsaturated polyester resin hybrid nano composites Sihama Issa Salih1, Waleed Bdaiwi Salih2, Husam Sakin Hamad2 - Sihama Issa Salih (Iraqi Journal of Physics, 2018)
In this work, two groups of nanocomposite material, was prepared from unsaturated polyester resin (UPE), they were prepared by hand lay-up method. The first group was consisting of (UPE) reinforced with individually (ZrO2) nanoparticles with particle size (47.23nm). The second group consists of (UPE) reinforced with hybrid nanoparticles consisting of zirconium oxide and yttrium oxide (70% ZrO2 + 30% Y2O3) with particles size (83.98nm). This study includes the effect of selected volume fraction (0.5%, 1%, 1.5%, 2%, 2.5%, 3%) for both reinforcement nano materials. Experimental investigation was carried out by analyzing the thermo-physical properties like thermal conductivity, thermal diffusivity and specific heat for the polymeric composites samples, as well as the hardness test. The results showed that the values of (hardness, specific heat) increased as the nanoparticle content in composite samples increased for both groups’ nanocomposites, whereas the values of thermal conductivity and thermal diffusion decrease for both groups composites. And it was found that the properties of composite materials reinforced by hybrid nanoparticles have higher properties as compared with their counterparts of other nanocomposite reinforced by zirconia nanoparticle. The morphology of the fracture surface was showed homogeneous micro structure formation for both groups composites, indicating a good compatibility between the matrix material and the reinforcement nanoparticles.